PERANAN POLA ASUH ORANG TUA TERHADAP PRESTASI BELAJAR SISWA DI SEKOLAH DASAR - Kurniawan, Bayu; Sri Wahyuni; Dyah Arti Mumpuni; Choiriyah Widyasari; Ernawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The low learning achievement of students in elementary schools causes the need for evaluation from all parties, not just from the school. So, it is necessary to involve parents in improving student learning achievement in elementary schools. This is where parenting styles play an important role in producing children's achievements in elementary school. This research is a Systematic Literature Review. This research used 10 articles published in 2021-2024 using strict inclusion and exclusion criteria. The results of this research are that parenting patterns and student achievement in elementary schools have a relationship that is simultaneous, significant, influential and has a big influence. Of the three parenting styles, namely permissive, democratic and authoritarian, this research shows that democratic parenting has the greatest influence on student achievement outcomes in elementary school.